The ethnobotony and local knowledge of sayur asem by the vegetable traders - Marina Silalahi; Riska Septia Wahyuningtyas (JPBIO (Jurnal Pendidikan Biologi), 2021)
The sayur asem is one of the traditional Indonesian dishes, especially the Betawi ethnic group. This study aims to document the local knowledge of vegetable traders in the Kranggan Mas market, the diversity of plants used as an ingredient in sayur asem. The method used in this research was a survey. Data were analyzed qualitatively and descriptively. The sayur asem is a soup-like vegetable that has a sour taste with the main ingredients of melinjo (Gnetum gnemon) leaves and seeds and tamarind fruit (Tamarindus indica). The total of 13 species belonging 12 genera and 10 families used to process of making sayur asem. The part of used to process of making sayur asem is dominated by fruits (8 species), followed leaves and tubers (each 2 species). The melinjo (G. gnemon) is the main ingredient in the making of sayur asem, while Alphinia galanga, Syzygium polianthum and Tamarindus indica are the main spices with a larger volume. The main ingredients and seasonings used mostly have antioxidant and antimicrobial activity and are therefore very good at supporting digestive tract health and providing healthful effects.Keywords: Antioxidant, antimicrobial, gnetum gnemom, tamarindus indica